Insider trading : global developments and analysis - Ali, Paul A. U.; Gregoriou, Greg N. (Boca Raton, Fla. : CRC ; London : Taylor & Francis [distributor], 2009)
This book brings together some of the latest research on insider trading, covering U.S., European and Australasian market as well as the key emerging markets of Brazil and China.The book combines a variety of approaches toward the study of insider trading, with the contributors coming from the fields of accounting, economics, finance and law.
"A Chapman & Hall book."
Includes bibliographical references and index.
osa14/05/13
Loans
Keywords: Insider trading in securities; Trading - securities